Cholinergic Deficit Induced by Central Administration of 192IgG-Saporin Is Associated With Activation of Microglia and Cell Loss in the Dorsal Hippocampus of Rats - Dobryakova, Yulia V.; Volobueva, Maria N.; Manolova, Anna O.; Medvedeva, Tatiana M.; Kvichansky, Alexey A.; Gulyaeva, Natalia V.; Markevich, Vlamidir A.; Stepanichev, Mikhail Yu.; Bolshakov, Alexey P. (Frontiers in Neuroscience, 2019)
Alzheimer’s disease (AD) is associated with degeneration of cholinergic neurons in the basal forebrain. Administration of the immunotoxin 192IgG-saporin to rats, an animal model of AD, leads to degeneration of cholinergic neurons in the medial septal area. In the present study cholinergic cell death was induced by intracerebroventricular administration of 192IgG-saporin.1.5 months after injection, we studied the histopathology of the hippocampus and the responses of microglia and astrocytes using immunohistochemistry and neuroglial gene expression. We found that treatment with 192IgG-saporin resulted in neuronal loss in the CA3 field of the hippocampus. Microglial proliferation was observed in the dentate gyrus of the dorsal hippocampus and white matter. Massive proliferation and activation of microglia in the white matter was associated with strong activation of astrocytes. However, the expression of microglial marker genes significantly increased only in the dorsal hippocampus, not the ventral hippocampus. These effects were not related to nonspecific action of 192IgG-saporin because of the absence of Nerve growth factor receptor in the hippocampus. Additionally, 192IgG-saporin treatment also induced a decrease in the expression of genes that are associated with transport functions of brain vascular cells (Slc22a8, Ptprb, Sdpr), again in the dorsal hippocampus but not in the ventral hippocampus. Taken together, our data suggest that cholinergic degeneration in the medial septal area induced by intracerebroventricular administration of 192IgG-saporin results in an increase in the number of microglial cells and neuron degeneration in the dorsal hippocampus.